Implementasi Pembelajaran Berdiferensiasi Dalam Model Pembelajaran Jigsaw Untuk Meningkatkan Hasil Belajar Matematika Pada Materi FPB Dan KPK di Kelas V SD Plus IGM Palembang - Riska Andina; Mefi Laranti; Evy Ratna Kartika Waty; Sohamah (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2023)
This research aims to determine whether or not student learning outcomes have improved in mathematics subjects such as FPB and KPK material by implementing differentiated learning in the jigsaw learning model. Where the subject under study obtained learning outcomes that were less than or below the school's criteria for achieving learning objectives, therefore classroom action research was carried out using the jigsaw model. The type of research used is Classroom Action Research (CAR). The implementation stage of classroom action research (CAR) includes activities: planning, implementation, observation and reflection. The instrument used in data collection is a formative test which is carried out after the learning process which applies the jigsaw model. Data analysis was carried out using descriptive analysis (average and percentage). Meanwhile, the criteria for learning completeness are based on a score that exceeds the school's criteria for achieving learning objectives. This research was carried out in three cycles with improvements or changes in each cycle. In cycle I, 52.17% of students completed learning using the jigsaw model, in cycle II, 73.91% of students completed learning using jigsaw model, and in cycle III, 91.30% of students completed learning. which was completed after following the lesson using the jigsaw model. Based on the description above, it can be concluded that the application of differentiated learning in the jigsaw learning model can improve student learning outcomes in mathematics subjects in class V SD Plus IGM Palembang.